1999
DOI: 10.1111/1467-8624.00008
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Report of Vocabulary and Grammatical Development of African American Preschoolers: Child and Environmental Associations

Abstract: This study examined how child and family factors affect individual differences in the language development of African American children between 18 and 30 months of age. Participants were 87 African American children, primarily from low-income families. Children's vocabulary and grammatical skills were assessed at 18, 24, and 30 months of age using the short form of the MacArthur Communicative Development Inventory (CDI), a standardized parent report tool. Standardized language tests were administered repeatedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 42 publications
2
51
0
7
Order By: Relevance
“…Building on Hart and Risley's (1995) findings based on 6 families, the results of this study of 108 families adds to a growing body of literature documenting considerable variability in observed maternal talk to children, even within low-income groups (DeTemple & Snow, 1996;Pan & Rowe, 1999). These analyses complement research findings based on observer ratings (Roberts et al, 1999) and raise two other issues: how stable individual mothers are in the communicative input they offer children over toddlerhood, and what specific factors relate to variability in maternal input.…”
Section: Variation In Communicative Inputmentioning
confidence: 66%
See 1 more Smart Citation
“…Building on Hart and Risley's (1995) findings based on 6 families, the results of this study of 108 families adds to a growing body of literature documenting considerable variability in observed maternal talk to children, even within low-income groups (DeTemple & Snow, 1996;Pan & Rowe, 1999). These analyses complement research findings based on observer ratings (Roberts et al, 1999) and raise two other issues: how stable individual mothers are in the communicative input they offer children over toddlerhood, and what specific factors relate to variability in maternal input.…”
Section: Variation In Communicative Inputmentioning
confidence: 66%
“…Until quite recently, Hart and Risley's (1995) detailed study of 6 welfare-eligible families and their children, followed through child age 3, and the Home School Study of Language and Literacy Development (DeTemple & Snow, 1996;Dickinson & Tabors, 2001) of 74 families beginning when children were preschoolers, represented the bulk of longitudinal work on spontaneous parent -child verbal interaction in low-income families. A number of other studies were either cross-sectional in design and/or involved very small samples (e.g., Barnes, Gutfreund, Satterly, & Wells, 1983;Pan & Rowe, 1999), or were based only on observer ratings of mother -child verbal interaction (Roberts, Burchinal, & Durham, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…12 Some studies have reported that children of lower socio-economic condition have a poor performance in language, vocabulary and articulation tests, and such results have been related to their social conditions. 8,14 A statistically significant association was observed between the child's age and better performance in the PPVT. Older children had better results in the test.…”
Section: Discussionmentioning
confidence: 94%
“…With a few notable exceptions (e.g. Roberts, Burchinal & Durham, 1999;Feldman et al, 2000), most research to date has focused on children from middle-class families or on small groups of children from working-class or low-income families (e.g. Hart & Risley, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, concerns have been raised about the validity of parental report, particularly with respect to minority and low-income families (Arriaga, Fenson, Cronan & Pethick, 1998 ;Roberts et al, 1999 ;Feldman et al, 2000). One means of assessing the validity of parental report is by examining its concurrent and predictive association with other measures of P A N E T A L. vocabulary, language, or cognitive development.…”
Section: Introductionmentioning
confidence: 99%